Rare Earth Elements As Emerging Catalysts: A Review Of Their Role In Enhancing Dlfc And Pemfc Performance - Zatil Amali Che Ramli; Jagadeesh Pasupuleti; Salma Samidin; Tengku Shafazila Tengku Saharuddin; Wan Nor Roslam Wan Isahak; Sieh Tiong Kiong (Elsevier, 2026)
Indexed by WOS / SCOPUS / ERA